Policing human rights: an analysis of law enforcement responses to trafficking in persons in the UK and Nigeria - McGeer, CA (2022)
This thesis focuses on how public police identify victims and offenders of human trafficking in the UK and Nigeria. I contribute to the field of critical trafficking studies in this thesis by exploring how police understand and respond to human trafficking. I also contribute methodologically by engaging in primary data collection in two countries, one of which is conceptualized as primarily a source country, Nigeria, and the other a destination country, the UK. I selected these countries because of the historical and contemporary linkages between the two related to the foundations of their policing culture, estimates of trafficking, and governance of their trafficking responses. I draw on 60 interviews with police officers and their partners and analysis of 887 police case files to explore how UK and Nigerian police make sense of who victims and offenders are when they are on the job. I analyze the culture and practice of police on the ground when they are responding to human rights violations. I found that although police in the UK and Nigeria have different approaches to conceptualizing victims and offenders and that the differences in approaches do matter, they both fail to recognize and respond to the needs of vulnerable people. I argue that police responses to human trafficking reflect the performative, humanitarian aspects of anti-trafficking rhetoric. These responses result in further rights violations for vulnerable people. I find that law enforcement responses to trafficking are sites of state exercises of territoriality.